Mielcke or Milkus, or How to Write Prussian Lithuanian Personal Names of Non-Lithuanian Origin? - Sidabraitė, Žavinta (Colloquia, 2021)
The history of the adaptation of the surname of Christian Gottlieb Mielcke (1733-1807), one of the most important creators of Lithuanian language and literature at the turn of the 19th century, covers the period from the 19th century to the present day. The adaptation of this personal name of non-Lithuanian origin has undergone probably the biggest changes in Lithuanian culture. Today, we count eight different variants of its usage: Mielcke, Mielckė, Mielke, Mielkus, Milkė, Mylkė, Milkus, and Mielcke’ė. In the 20th century, two variants were the most common: Milkė in the interwar period and the first years after the war and Milkus from the mid1960s. Jurgis Lebedys (1913-1970), the most authoritative researcher of old Lithuanian literature and a lecturer at Vilnius University, introduced this form in the Lithuanian language. Adapted following the example of the popular Prussian Lithuanian name (not surname!), the form took root rather quickly and easily not only in Lithuania but also in the diaspora. After Lithuania regained its independence at the end of the 20th century and when the world of the Western culture opened up, two groups of researchers formed. One group advocates the original form Mielcke and implement it in their works, while other group, trying to preserve the connection with the long tradition of Lithuanian research, uses the adapted form, Milkus. As a single drop reflects the entire ocean, so the tradition of the use of the personal name Mielcke’ė and today’s practice reveal the problem of the use of personal names of all famous Lithuanian writers of non-Lithuanian origin. It can only be solved by an extensive scientific discussion.
Keywords: literary history; literature; personal name; adaptation; Lithuania; Jurgis Lebedys; Prussian Lithuanian.